Diagnóstico del turismo de naturaleza en complejos de páramo de Colombia (2023)
The páramos in Colombia are areas dedicated to the protection and conservation taking into account their ecosystem importance, the environmental services it provides and its contribution to the mitigation of climate change. The regulations relate the delimitation, the guidelines, as well as the prohibited activities to guarantee integrality, preservation, restoration, sustainable use and generation of knowledge of these complexes, however, industrial, mining, agricultural and livestock projects are developed, among others, that impact on the ecosystem.